Kewenangan Mahkamah Kostitusi dalam Memutus Usulan Impeachment Presiden dan/atau Wakil Presiden dalam Hukum Positif di Indonesia - Nurjamil, Faisal Faturrahman (Lembaga Yasin AlSys, 2023)
Impeachment is an indictment or indictment against the president or a high-ranking state official from office. One of the powers of the Constitutional Court, which is commonly referred to as an obligation, is to give a decision on the opinion of the House of Representatives regarding alleged violations by the President and or Vice President. The nature of the decision issued by the Constitutional Court is juridically final. The decision of the Constitutional Court lies in its relative nature or has no binding legal force for the People's Consultative Assembly as a state institution that is at the end of the case process of dismissal of the President and / or Vice President during his term of office to follow the decision of the Constitutional Court, except in the case of holding a plenary meeting as proposed by the House of Representatives. This is an implication of Article 7B paragraph (6) of the Constitution of the Republic of Indonesia Year 1945. The authority or obligation of the Constitutional Court towards the Impeachment proposal by the House of Representatives is a normative effort so as not to repeat the dismissal of the President and / or Vice President which is only based on slander and suspicion in order to satisfy political martyrdom.